Contextual factors influencing external and internal training loads in collegiate men's soccer - Curtis, R. M.; Huggins, R. A.; Benjamin, C. L.; Sekiguchi, Y.; Adams, W. M.; Arent, S. M.; Jain, R.; Miller, S. J.; Walker, A. J.; Casa, D. J. (The Journal of Strength and Conditioning Research, 2020)
This study investigated factors influencing training loads (TL) in collegiate men's soccer. Total distance, high-speed running distance (>14.4 km·h-1), high-intensity heart-rate zone duration (HI HRZ, >70% heart rate relative to maximum), and session rating of perceived exertion were assessed daily from 107 male soccer players competing for 5 National Collegiate Athletics Association Division I teams. Differences between athlete role (starter and reserve), position (defender, midfielder, and forward), season phase (preseason, in-season, and postseason), days relative to match (MD-1 to MD-5+), days between matches (<4, 4-5, >5 days), previous match outcome (win, loss, and draw), and upcoming opponent relative ranking (weaker, trivial, and stronger) were examined. Mean differences (MD) and effect sizes (ESs) with 90% confidence intervals were reported. There were trivial and insignificant differences by player role, position, or upcoming opponent strength, and small-moderate increases in preseason TL compared with in-season (ES [range] = 0.4-0.9). TLs were lower for MD-1 and higher for MD-5+ (ES [range] = 0.4-1.3) when compared with MD-2-4. External loads (ES = -0.40 ± 0.20) were less after wins compared with losses. TLs are increased in the preseason, when training sessions occur greater than 5 days from a match and after losses. Contextualizing factors affecting TLs has implications for developing workload prescription and recovery strategies.